Cluster Partition-Based Zonal Voltage Control for Distribution Networks With High Penetrated PVs - Zhao, Xingyu; Xiao, Chuanliang; Peng, Ke; Chen, Jiajia; Zhang, Xinhui (Frontiers in Energy Research, 2022)
With the high penetrated photovoltaics (PVs) accessing distribution networks (DN) in the future, the overvoltage of distribution network will be more serious, and the voltage control will be more complex. To solve this problem, a cluster partition based zonal voltage control method for DN is proposed in this paper. Firstly, a cluster partition method using comprehensive performance index is proposed: In terms of DN structure, a global density quality function index is introduced to measure the coupling degree of nodes in clusters. In terms of cluster function, the inconsistency coefficient index is presented to reflect the PV output characteristics, and a node membership function index is presented to limit the scale of the cluster. Then, and the DN cluster partition is carried out under the Fast Newman (FN) algorithm. Secondly, a second-order cone programming (SOCP) model of voltage control is established to maximize the PV consumption in each cluster. And to achieve the coordinated optimization of clusters, an iterative optimization strategy among clusters is proposed. Finally, the effectiveness and rationality of the proposed method are verified in a 10kV actual feeder system in Zhejiang Province, China.